A morphological review of the jellyfish genus Nausithoe Kölliker, 1853 (Nausithoideae, Coronatae, Scyphozoa, Cnidaria) - Molinari, Clarissa G.; Collins, Allen G.; Morandini, André C. (Zootaxa, 2023)
In this study we address the diversity of the scyphozoan jellyfish genus Nausithoe Kölliker, 1853 (Nausithoidae, Coronatae), questioning the feasibility of using some characters of the medusa stage to identify species and filling in gaps concerning species of the genus and their distributions. Like most scyphozoans, the vast majority of the 21 Nausithoe species have a metagenetic life cycle, but similarity of most polyps within the genus highlights the need for studying morphology of the medusa stage. By analyzing morphological features on preserved and live specimens (polyps and medusae) and comparing these data with the original descriptions, we were able to validate twenty species of the group, providing new information for some of them.